2014
DOI: 10.1111/jeb.12300
|View full text |Cite
|
Sign up to set email alerts
|

Renewed diversification is associated with new ecological opportunity in theNeotropical turtle ants

Abstract: Ecological opportunity, defined as access to new resources free from competitors, is thought to be a catalyst for the process of adaptive radiation. Much of what we know about ecological opportunity, and the larger process of adaptive radiation, is derived from vertebrate diversification on islands. Here, we examine lineage diversification in the turtle ants (Cephalotes), a species-rich group of ants that has diversified throughout the Neotropics. We show that crown group turtle ants originated during the Eoce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
69
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(73 citation statements)
references
References 121 publications
4
69
0
Order By: Relevance
“…within some ant subfamilies (Schultz & Brady 2008;Ward et al 2010Ward et al , 2014Schmidt 2013;Brady et al 2014) and larger genera (Moreau 2008, Jansen et al 2010, Blaimer 2012, Branstetter 2012, Price et al 2014. These studies at shallower taxonomic levels have employed more extensive taxon sampling, which has enhanced inferences about diversification, biogeographic history, and trait evolution.…”
Section: Wwwannualreviewsorg • Ant Phylogeny and Evolution 37mentioning
confidence: 99%
“…within some ant subfamilies (Schultz & Brady 2008;Ward et al 2010Ward et al , 2014Schmidt 2013;Brady et al 2014) and larger genera (Moreau 2008, Jansen et al 2010, Blaimer 2012, Branstetter 2012, Price et al 2014. These studies at shallower taxonomic levels have employed more extensive taxon sampling, which has enhanced inferences about diversification, biogeographic history, and trait evolution.…”
Section: Wwwannualreviewsorg • Ant Phylogeny and Evolution 37mentioning
confidence: 99%
“…; Price et al. ). Conversely, a lack of signal has been attributed to the geographic and ecological complexity of continents, with ecological saturation unlikely to occur on such a scale (Derryberry et al.…”
mentioning
confidence: 97%
“…, although not always; Price et al. ), even showing multiple EO events nested across subclades (Drummond et al. ; McGuire et al.…”
mentioning
confidence: 99%
“…Turtle ants (genus Cephalotes) represent a highly diverse and species-rich neotropical clade (Price et al, 2014). Studies using PCR amplification and DNA sequencing techniques have revealed that Cephalotes ants harbor a core gut microbiota (Anderson et al, 2012;Hu et al, 2014;Kautz et al, 2013;Russell et al, 2009).…”
mentioning
confidence: 99%